Transformational Leadership and Employee Creativity Impact on Employee Performance in the Media Industry: Work Engagement Mediation - Muhamad Yusuf Rusli; Pribadi, Bangkit Rizki Beny; Yakin Rahmat Zebua; Nugroho Juli Setiadi (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of transformational leadership and employee creativity on employee performance in Indonesia's media industry, mediated by work engagement. Utilizing a quantitative cross-sectional survey with 114 valid responses, data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that employee creativity and work engagement significantly enhance employee performance. However, transformational leadership showed non-significant direct effects on performance and engagement, and work engagement did not mediate these relationships. Consequently, media organizations should prioritize practical job resources, creative support, and robust production systems over solely inspirational leadership to drive employee performance. Keywords: Transformational Leadership; Employee Creativity; Work Engagement; Employee Performance; Media Industry; PLS-SEM